Analysis of the Use Teleconsultation in Teledentistry for Dentist Practice against UU Number 17 of 2023 - Sembiring, Tamaulina Br.; Hasibuan, Siti Aminah (PT FORMOSA CENDEKIA GLOBAL, 2024)
In the context of the Fourth Industrial Revolution, which intertwines biological and digital advancements, technologies like teledentistry are revolutionizing healthcare delivery in Indonesia. Teledentistry enables remote dental and oral health services through methods such as teleconsultation, teleeducation, telemonitoring, and telesurgery (Anggayanti et al., 2023). Legislation such as Law Number 17 of 2023 on Health Management in Indonesia plays a pivotal role in regulating teledentistry and ensuring patient and dentist protection. This law outlines the rights of patients to receive safe, quality, and affordable healthcare services, encouraging the use of information and communication technologies in healthcare delivery (Amril, 2023). The normative legal approach utilized in this study examines primary and secondary legal materials to analyze the implications of Law Number 17 of 2023 on teledentistry practices.This study concludes that teleconsultation in teledentistry is a valuable tool for overcoming geographical barriers and improving access to dental care in Indonesia. However, further specific legislation is recommended to foster patient trust and optimize the use of teledentistry for achieving optimal dental and oral health outcomes.